Post COVID-19 Learning Adaptation: Teachers’ Strategies and Innovations in Teaching English in the Post Pandemic - Wahyu Adri Wirawati; Roudlotun Nurul Laili; Muhammad Nashir (EduLine: Journal of Education and Learning Innovation, 2022)
Limited Face-to-face Learning is a government initiative program to solve the problem of learning loss during online learning in the Covid 19 outbreaks by implementing strict health protocol procedures to prioritize student safety. This research aimed to describe the preparation for learning in the new normal period, explore the practice of limited face to face learning in English subject, and teachers’ strategies in teaching English in the post pandemic. This research used a descriptive qualitative method with a case study with the total respondents were 45 English teachers of Senior high school in Banyuwangi. The data needed was obtained through questionnaire and interview. The findings showed that the implementation of limited face to face learning had followed the government rules in the new normal period. English teaching learning process had generally been going well and was presented through several interesting strategies and fun methods, although a number of obstacles arise such as the reduction in school hours and the division of student groups or shifts in the learning process which encouraged the teachers to apply blended learning by still utilizing learning platforms in their teaching. The most favorable learning platform was Whatsapp.